2003
DOI: 10.1007/s10144-003-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the solitary digger bee Andrena vaga Panzer (Hymenoptera, Andrenidae) studied using mark‐recapture and nest counts

Abstract: The population size of the solitary digger bee Andrena vaga was documented using mark‐recapture methods during 4 consecutive years (1996–1999). Additionally, the numbers of the parasitoids Nomada lathburiana and Bombylius major were estimated. For calculations of the daily population size, the Jolly‐Seber model for open populations with time‐dependent survival and capture rates was used. The mean daily population size corresponded well to the number of nests marked in the aggregation of A. vaga. The method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
0
19
1
1
Order By: Relevance
“…While recapture rates found in the present study are well within the range of recaptures measured for species of other insect groups in search of their key resources (Toepfer et al, 1999(Toepfer et al, , 2000Haddad et al, 2008), they are lower than those reported in other studies with pollen specialist bee species (Bischoff, 2003;Franzen et al, 2009).…”
Section: Discussioncontrasting
confidence: 51%
“…While recapture rates found in the present study are well within the range of recaptures measured for species of other insect groups in search of their key resources (Toepfer et al, 1999(Toepfer et al, , 2000Haddad et al, 2008), they are lower than those reported in other studies with pollen specialist bee species (Bischoff, 2003;Franzen et al, 2009).…”
Section: Discussioncontrasting
confidence: 51%
“…Hence, a high rate of dispersal might compensate for local extinctions. This hypothesis is supported by the fact that about 50% of the emerging females of Andrena vaga are known to emigrate (Bischoff 2003).…”
Section: Discussionmentioning
confidence: 74%
“…Mark-recapture experiments are widely used in population ecology for estimating parameters such as population size, survival rates, longevity and dispersal (Andres and Rivera, 2001;Bischoff, 2003) among others. However, these parameters have not been estimated for euglossine populations because of the low or non-existent recapture rates when bees are marked at chemical baits (Kroodsman, 1975;Janzen, 1981;Ackerman and Montalvo, 1985;Folsom, 1985;Raw, 1989;Eltz et al, 1999;Otero and Sandino, 2003;Tonhasca et al, 2003).…”
Section: Introductionmentioning
confidence: 99%